NILAI MANFAAT HUTAN MANGROVE DI DESA SAUSU PEORE KECAMATAN SAUSU KABUPATEN PARIGI MOUTONG - Motoku, Abner Widoyo; Umar, Syukur; Toknok, Bau (Universitas Tadulako, 2014)
Mangrove forest is a typical ecosystem in tropical regions, which have multiple benefits and effects especially on the social, economic and ecological aspects. This study was aimed to know direct and indirect benefits of mangrove forest by analyze and quantify its value to Indonesian currency (IDR). The study was conducted at Sausu Peore village, Sausu sub-district, Parigi Moutong regency, Central Sulawesi, from March through May 2014. The method used in this study was based on the market price. Respondents were selected by purposive sampling method. Identification and quantification of the use natural resources was done by assessment on the market and replacement price. The results showed that direct benefits of the mangrove forests in this area are firewoods, wood as construction materials, fishs, shellfish, crabs, and bats, while indirects benefits of the mangrove forests is as a buffer on coastal aberration. The economic value of direct benefits was IDR. 513,499,753, while the value of indirect benefits was IDR. 499,655,240, so the total value of all benefits was IDR.1,013,164,993. Keywords: Direct Benefit, Indirect Benefit, Mangrove, Economic Value